The list-wide proportion congruency effect is larger when the distractor precedes the target: Evidence for conflict-independent control in the prime-probe task. - Weissman, Daniel H.; Saba, Chloe E. (Memory & Cognition, 2025)
Stroop-like interference effects are smaller in blocks of mostly incongruent (MI) trials than in blocks of mostly congruent (MC) trials. It is unclear, though, how control processes trigger this list-wide proportion congruency effect (LWPCE). The attentional shift account posits that a memory of experiencing conflict more frequently in MI blocks than in MC blocks leads control processes to shift attention toward the target in MI blocks. The response modulation account posits that a memory of block-wide congruency statistics (e.g., mostly incongruent) leads control processes to form expectations about upcoming trial congruency independent of conflict and modulate distractor-related response activation to prepare an expected congruent response (in MC blocks) or incongruent response (in MI blocks) to the target. This modulation occurs, however, only if the system translates the distractor into a response before the target. We conducted two experiments with the prime-probe task (N = 120) to investigate the response modulation account's prediction that giving the distractor a "head start" in stimulus–response translation increases the LWPCE independent of conflict. Confirming this prediction, the LWPCE was larger when the distractor appeared before – versus simultaneously with – the target, even though the overall congruency (i.e., conflict) effect was equivalent in these conditions (Experiment 1) or smaller when the distractor appeared before the target (Experiment 2). We also observed a negative congruency effect in the MI blocks of Experiment 2, which is inconsistent with a shift of attention toward the target. We conclude that a modulation of response activation contributes to the LWPCE.